Disruption in Essential Health Service Delivery: A Qualitative Study on Access to Family Planning Information and Service Utilization During the First Wave of COVID-19 Pandemic in Uganda - Kabagenyi, Allen; Kyaddondo, Betty; Nyachwo, Evelyne Baelvina; Wasswa, Ronald; Bwanika, John Mark; Kabajungu, Enid; Kiragga, Agnes (Open Access Journal of Contraception, 2022)
Background Coronavirus disease 2019 (COVID-19) remains a challenge to public health with profound impact on people’s lives. With several mitigation measures implemented to curb the spread of COVID-19, these impacted on access and utilization of general health services including family planning (FP) services. The objective of the study was to understand the extent to which COVID-19 interrupted access and utilization of FP services as well as highlight the challenges faced during the lockdown in Uganda. Methods A qualitative study was carried out in August and September 2020 across the country. A total of 21 key informant interviews among researchers, policy makers, funding agencies, district family planning focal persons, district health officers and service providers with implementing partners were conducted. These were conducted using face to face (7), phone calls (11) and zoom (3) meetings. All interviews were audio recorded and transcribed verbatim. Transcripts were used to identify and generate codes, sub themes and themes. Analysis was done using the thematic framework analysis and results presented in themes. Results Five themes were identified in this study which included; (i) financial and psychosocial needs, (ii) mobility hindrances, (iii) disrupted service delivery, (iv) responsive reproductive health services. The financial and psychosocial needs themes included: household and individual financial constraints, unpredictable future and community acceptance, loss of employment and unemployment, misconceptions and unintended pregnancies; while mobility hindrances included; restricted movement, high transport costs, and difficulty in finding transport. Conclusion Results showed that the pandemic had immediate and significant long-term effects on family planning service accessibility, utilization and delivery. The study recommends implementation of telehealth services, country-wide sensitization on use of long-term contraceptive methods, empowering village health teams and making family planning services mandatory and free to all private facilities in order to lower any disruptions during pandemics.